A giant left atrial mass—Clinical treatment dilemma. Issue 6 (22nd May 2019) - Hsi, David H.; Ebright, Michael I.; Del Prete, Salvatore A.; Pearson, Gregory; Bernstein, Michael A.
Abstract: A 74‐year‐old female current 75 pack‐year smoker presented with shortness of breath and mild hemoptysis. Chest computed tomography showed a large right upper lobe mass compressing the superior vena cava, invading the right pulmonary veins, and occupying the majority of the left atrium. Brain magnetic resonance imaging revealed a 13 mm right parietal lesion with surrounding edema consistent with metastasis. A 3D TEE showed a large mobile mass in the left atrium. Bronchoscopy confirmed that the tumor mass was consistent with a moderately to poorly differentiated squamous cell carcinoma. She underwent chemotherapy, radiation, and immune therapy. She was also started on warfarin for anticoagulation after the initial chemotherapy with resolution of the left atrial mass. We feel that the patient most likely had carcinogenic thrombus in the pulmonary veins and left atrium.